Research on the Risk of Drilling Phases Based on the Development Model of Shallow-Water Subsea Trees - Zhiming Yin; Meipeng Ren; Yingwen Ma; Xiangqian Yang; Deqiang Tian; Haiwei Wang; Chengcheng Xiao; Jingyu Qu (Journal of Marine Science and Engineering)
China is actively advancing offshore oil and gas exploration and development, focusing on addressing the technical challenges associated with resource extraction in shallow waters. The shallow-water subsea tree development model has gradually been applied in such environments, alleviating some construction difficulties. However, it still poses well control risks that require systematic analysis and quantitative evaluation. Given that the blowout preventer (BOP) is located on the platform and the shallow-water subsea tree is only used during certain drilling stages, this study divided the drilling process into two phases: the first three sections and the fourth section. Based on the “man–machine–material–environment” analytical framework and an improved system-theoretic process analysis (STPA), a control model for the construction phases was developed. Fault tree analysis (FTA) was then employed to identify comprehensively the potential risks from the platform to the wellbore in both phases. Subsequently, the decision-making trial and evaluation laboratory (DEMATEL) method were used to assess quantitatively the well control risks. Using the average weight as the evaluation criterion, high-risk factors exceeding the average weight in each phase were identified. The results indicate that in the shallow-water subsea tree development model, well control risks in the first three drilling sections primarily stem from human errors and equipment failures, while risks in the fourth section are mainly caused by damage to the subsea tree itself. The identified risk factors provide a theoretical basis for enhancing well control safety management in the shallow-water subsea tree development model.